2014
DOI: 10.2147/tcrm.s50362
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of acarbose in the treatment of diabetes in Chinese patients

Abstract: Acarbose is an α-glucosidase inhibitor that is commonly used to control postprandial blood glucose. It functions as a competitive and reversible inhibitor of small intestinal brush border glucosidase, blocks the degradation of starch and sucrose, and delays the absorption of glucose and fructose in the alimentary tract. The starch content of a diet might alter the hypoglycemic effects of acarbose because of its mechanism of action. Chinese individuals consume a typical Eastern diet, which is characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Moreover, in previous studies, these fatty acids showed remarkable inhibition on α-glucosidase enzyme, which was significantly higher than acarbose [27,35]. Therefore, C. indica fruits could be predicted as having potential for anti-α-glucosidase activity, which is involved in the prevention of hyperglycemia [36]. If that is the case, a comprehensive solution for type 2 diabetes avoidance could be exploited from C. indica fruits.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in previous studies, these fatty acids showed remarkable inhibition on α-glucosidase enzyme, which was significantly higher than acarbose [27,35]. Therefore, C. indica fruits could be predicted as having potential for anti-α-glucosidase activity, which is involved in the prevention of hyperglycemia [36]. If that is the case, a comprehensive solution for type 2 diabetes avoidance could be exploited from C. indica fruits.…”
Section: Discussionmentioning
confidence: 98%
“…The α-glucosidase inhibitors (AGIs) primarily reduce postprandial plasma glucose concentrations through the competitive and reversible inhibition of α-glucosidase located in the brush border of the small intestine 60. Following nutrient ingestion, α-glucosidase hydrolyzes complex carbohydrates to monosaccharides for absorption.…”
Section: Actions Of Commonly Used Antidiabetes Medicationsmentioning
confidence: 99%
“…Following nutrient ingestion, α-glucosidase hydrolyzes complex carbohydrates to monosaccharides for absorption. Thus, AGIs obstruct the degradation of starches and sucrose and delay carbohydrate reabsorption in a nonsystemic manner 60. However, a patient’s diet may alter efficacy.…”
Section: Actions Of Commonly Used Antidiabetes Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acarbose is a type of noninsulinotropic oral antidiabetic drug molecule, which mainly used to treat type two diabetes [1]. It is mainly used with a proper diet supplemented food and regular exercise to control the blood sugar in humans [2]. Acarbose also helps to prevent kidney damage, blindness, nerve cord problem, and other performance via controlling high blood sugar.…”
Section: Introductionmentioning
confidence: 99%